2015
DOI: 10.1111/maec.12266
|View full text |Cite
|
Sign up to set email alerts
|

The role of life‐history traits, selective pressure and hydrographic boundaries in shaping the genetic structure of the transparent goby, Aphia minuta

Abstract: The transparent goby (Aphia minuta) is a small progenetic goby that displays a short life cycle with early reproductive maturity and represents a valuable fishery resource harvested by artisanal fleets in most part of its distributional range. This study aimed to define the genetic variability in A. minuta at five sampling sites within the Mediterranean Sea and one in the Atlantic Ocean through the analysis of 11 nuclear microsatellite loci. The results revealed that several genetic diversity estimators (expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…This is particularly true for marine pelagic fish species where the identification of population structure is hampered by the low level of intraspecific heterogeneity ( Ward, Woodwark & Skibinski, 1994 ) as a result of the absence of geographical barriers, long larval periods and their widespread dispersal as well as highly migratory adults that facilitate high levels of gene flow. However, demographic history of the ancestral population combined with current ecological biogeographic factors, such as dispersal potential, spawning behaviour and population size, have led to population differentiation, as revealed by several genetic studies for different fish species ( Zardoya et al, 2004 ; Martínez et al, 2006 ; Ruzzante et al, 2006 ; O’Leary et al, 2007 ; Pecoraro et al, 2016 ; Pecoraro et al, 2018 ; Ruggeri et al, 2016a ; Ruggeri et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for marine pelagic fish species where the identification of population structure is hampered by the low level of intraspecific heterogeneity ( Ward, Woodwark & Skibinski, 1994 ) as a result of the absence of geographical barriers, long larval periods and their widespread dispersal as well as highly migratory adults that facilitate high levels of gene flow. However, demographic history of the ancestral population combined with current ecological biogeographic factors, such as dispersal potential, spawning behaviour and population size, have led to population differentiation, as revealed by several genetic studies for different fish species ( Zardoya et al, 2004 ; Martínez et al, 2006 ; Ruzzante et al, 2006 ; O’Leary et al, 2007 ; Pecoraro et al, 2016 ; Pecoraro et al, 2018 ; Ruggeri et al, 2016a ; Ruggeri et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Also in the case of the transparent goby, Aphia minuta, the studies carried out on the microsatellite DNA showed a clear genetic structure, with the presence of two main populations (Atlantic and Mediterranean) and a probable further subdivision between the western Mediterranean and the Adriatic basins. This structure would seem to be shaped by the presence of oceanographic barriers that limit the exchange of individuals and consequently the gene flow between the different areas [54,113]. The presence of the Strait of Gibraltar and/or the Almeria-Oran front would have determined the isolation of the Mediterranean Sea from the Atlantic Ocean [89], while the separation between the western Mediterranean and the Adriatic Sea could be due to the presence of hydrographic barriers such as the narrow Sicilian-Tunisian and/or Otranto straits and the cyclonic circulation of the Ionian Sea [113].…”
Section: Evolution and Conservation Strategies: Examples From Vertebratesmentioning
confidence: 99%
“…This structure would seem to be shaped by the presence of oceanographic barriers that limit the exchange of individuals and consequently the gene flow between the different areas [54,113]. The presence of the Strait of Gibraltar and/or the Almeria-Oran front would have determined the isolation of the Mediterranean Sea from the Atlantic Ocean [89], while the separation between the western Mediterranean and the Adriatic Sea could be due to the presence of hydrographic barriers such as the narrow Sicilian-Tunisian and/or Otranto straits and the cyclonic circulation of the Ionian Sea [113]. Also the studies on swordfish (Xiphias gladius) populations led to a new understanding of the stock structure of this large pelagic fish, rejecting the hypothesis of a single Mediterranean population (Righi et al in preparation).…”
Section: Evolution and Conservation Strategies: Examples From Vertebratesmentioning
confidence: 99%
“…A. minuta and P. ferreri gobies are distributed in the European Atlantic from Gibraltar to the coasts of Norway and the Baltic Sea, and in the Mediterranean (Miller 1986, La Mesa et al 2005), whereas C. linearis is restricted to the Mediterranean (Wheeler 1992). The life history traits of A. minuta have been studied in the Mediterranean, including reproductive biology (Caputo et al 2001, 2003, Giovannotti et al 2007), age and growth (Iglesias et al 1997, La Mesa 1999, life cycle (Iglesias and Morales-Nin 2001) and population structure (Giovannotti et al 2009, Ruggeri et al 2016. C. linearis reproduction (Caputo et al 2003) and age and growth (La Mesa 2001) have been determined.…”
Section: Introductionmentioning
confidence: 99%